A comparative performance of antibacterial effectiveness of copper and silver coated textiles. (15th October 2022) - Ali, Azam; Petrů, Michal; Azeem, Musaddaq; Noman, Tayyab; Masin, Ivan; Amor, Nesrine; Militky, Jiri; Tomková, Blanka
During current COVID-19 crises, the antimicrobial textiles primarily those utilized in hospital by doctors and paramedical staff have become increasingly important. Thus, there is an unmet requirement to develop antimicrobial textiles for infection control and hygiene practices. Metallic nanoparticles exhibit great effectiveness towards resistant microbial species making them a potential solution to the increasing antibiotic resistance. Due to this, nanoparticles particularly copper and silver have become most prevalent forms of antibacterial finishing agents for the development of antimicrobial textiles. This review is mainly focused on the significance of copper and silver nanoparticles for the development of antimicrobial textiles. The comparative analysis of the antibacterial effectiveness of copper and silver nanoparticles as well as the possible physical and chemical interactions responsible for their antibacterial action are explained. The negative impact of pathogenic microbes on textiles and possible interactions of antimicrobial agents with microbes have also been highlighted. The significance of nanotechnology for the development of antimicrobial textiles and their applications in medical textiles domain have also been discussed. Various green synthesis and chemical methods used for the synthesis of Ag and Cu nanoparticles and their application on textile substrates to impart antimicrobial functionality have also been discussed. The various qualitative and quantitative standard testing protocols utilised for the antimicrobial characterization of textiles have also discussed in this review. The developed Cu and Ag coated textiles could be effectively applied in the field of hospital textiles for the preparation of antibacterial scrub suits, surgical gowns, panel covers, protective clothing, bedding textiles, coveralls, wound dressings, table covers, curtains, and chair covers etc.